Pengaruh Profitabilitas dan Reputasi Perusahaan terhadap Intellectual Capital Disclosure pada Industri Pariwisata di Indonesia - Ang Kezia Christabel; Daniella Britney; Saarce Elsye Hatane (Business Accounting Review, 2021)
This research aims to confirm the factors that can affect Intellectual Capital Disclosure(ICD) in tourism companies in Indonesia. This research uses 130 annual reports for the period yearfrom 2015 to 2019 from 26 companies listed on the Indonesia Stock Exchange (IDX) as researchsamples. The variables used in this research are ICD, firm profitability, firm reputation, firm size,and financial leverage. The measurement of ICD is done by using the content analysis method andthe research hypothesis is tested using panel data regression model. This research found that theHuman Capital Disclosure (HCD) component was the most disclosed component. In addition, thisstudy also finds that the company's profitability does not have a significant effect on the ICD, andthe company's reputation has a significant negative effect on the ICD. Meanwhile, the firm size andfinancial leverage have a significant positive effect on the ICD.